Ammonium sorption from aqueous solutions by the natural zeolite Transcarpathian clinoptilolite studied under dynamic conditions - Sprynskyy, M.; Lebedynet, M.; Terzyk, A.; Kowalczyk, Poitr; Namiesnik, J.; Buszewski, B. (Elsevier, 2005)
The scope of this study is ammonium-ion uptake from synthetic aqueous solutions onto raw and pretreated forms of the natural zeolite Transcarpathian clinoptilolite under dynamic conditions. Hydrogen ions displaced exchangeable cations on the clinoptilolite in distilled water (sodium ions) and hydrochloric acid (sodium, potassium, and calcium ions) and destroyed the zeolite framework structure in the last case. Ammonium uptake onto the zeolite occurs by exchange with Na+, Ca2+, and K+ ions. Although Na+ ions were observed to be more easily exchanged for both hydrogen and ammonium ions, the role of Ca2+ ions increased with zeolite saturation by NH+ 4 ions. The maximum sorption capacity of the clinoptilolite toward NH+ 4 ions, estimated under dynamic conditions, is significantly higher than that measured under static conditions; proximity of the values of a distribution coefficient and a retardation factor for different conditions (215–265 dm3/kg and 979–1107, respectively) allows us to use these parameters to model ammonium uptake onto the clinoptilolite. Slowing down or interruption in filtration resulted in the improvement of ammonium sorption properties of the zeolite. The ammonium removal improves with use of the finer fractions of the clinoptilolite up to 0.35 mm. A recycling study results confirmed the importance of external diffusion for ammonium sorption by the clinoptilolite. Preliminary treatment of the sorbent confirmed the predominant importance of the ion-exchange mechanism. The advantage of prior NaCl treatment of the clinoptilolite in improvement of ammonium removal over the other techniques was shown.